The determinants of mode of transport to work in the Greater Dublin Area - Nicola Commins; Anne Nolan (The Economic and Social Research Institute (ESRI), 2008)
Rapid economic and demographic change in the Greater Dublin Area over the last decade, with associated increases in car dependence and congestion, has focused policy on encouraging more sustainable forms of travel. In this context, knowledge of current travel patterns and their determinants is crucial. Here we concentrate on travel for a specific journey purpose, namely the journey to work. We employ cross-section micro-data from the 2006 Census of Population to analyse the influence of travel and supply-side characteristics, as well as demographic and socio-economic characteristics on the choice of mode of transport to work in the Greater Dublin Area.
Keywords: 330; Straßenverkehr; Verkehrsmittel; Arbeitsplatz; Öffentlicher Personennahverkehr; Kraftfahrzeug; Dublin